The creolization of American culture : William Sidney Mount and the roots of blackface minstrelsy - Smith, Christopher J. (Christopher John), 1959- (Music in American life., 2013)
This work examines the artworks, letters, sketchbooks, music collection, and biography of the painter William Sidney Mount (1807-1868) as a lens through which to see the multi-ethnic antebellum world that gave birth to blackface minstrelsy.